Hyperferritinemia at the patient with chronic hepatitis C - Ye. N. German; A. O. Buyeverov; M. V. Mayevskaya; Ch. S. Pavlov; V. T. Ivashkin; A. A. Levina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of clinical case presentation. To represent the patient with chronic hepatitis C with severe hyperferritinemia and absence of dominant mutations of hereditary hemochromatosis gene.Clinical case data. Patient К., 38 years, despite of rapid virologic response at combined antiviral therapy by pegilated interferon α-2а and ribavirin, had persistently high activity of transaminases and initially high level of serum ferritin increase twice.Conclusion. Retrospective evaluation of developed clinical situation allows to assume, that ferritin in this case acted as acute-phase protein. On the other hand, taking into account high level of serum transaminases and lymphadenopathy (developed at the 20-th week of treatment), atypical side effect of the antiviral agents of idiosyncrasy type can be suspected. After cessation of the treatment course clinical and laboratory abnormalities reduced. Sustained virologic response was ascertained.